Effect of FYM, foliar feeding of nitrogen and deficit irrigation on drip irrigated coriander (Coriandrum sativum L.) - K Balai, M P Sahu, I M Verma, S R Bhunia, N C Sharma, (Journal of Spices and Aromatic Crops, 2015)
A field experiment was conducted to study the water use, nitrogen (N) uptake and economics of coriander (Coriandrum sativum L.) under organic enrichment, foliar feeding of N and fertigation. Drip irrigation at 80% ETc + foliar spray of 25% N (15 kg ha-1) + fertigation (45 kg ha-1) gave the highest plant height, branch plant-1, umbel plant-1, umbelets umbel-1, seed umbel-1, and test weight compared to irrigation at 80% ETc and at 60% ETc (upto flowering stage) + 80% ETc (reproductive stage) with or without foliar spray. Increased yield parameters were attributed to the highest seed yield and B:C ratio of 1.90 using 265.74 mm water. Water use efficiency (WUE) was also the highest. This treatment also recorded the highest N uptake of 52.6 kg ha-1. Further, addition of 10 t ha-1 FYM in addition to recommended nitrogen dose (60 kg ha-1) gave higher yield attributes viz., branch plant-1, umbel plant-1, seed umbel-1 and test weight as compared to recommended level of fertilizers. Enhanced yield attributes thus increased seed yield, N removal, WUE and B:C ratio.